Fundamental issues in small and medium-sized enterprises - Hashim, Mohd Khairuddin (Universiti Utara Malaysia, 2010)
Fundamental Issues in Small and Medium-Sized Enterprises represents seven articles written based on recent research conducted on small and medium-sized enterprises(SMEs). The seven articles compiled in this ninth volume were originally papers presented at several international conferences. Each of the seven articles in the book emphasizes on a specific fundamental issue that is important to our understanding of SMEs. More significantly, these articles collectively provide useful insights into the issues that can help us to better understand the development, survival and growth of SMEs.